Agronomic Performance of three most Popular Commercial Watermelon Cultivars in Kenya as Compared to one newly introduced cultivar and one local Landrace grown on Dystric Nitisols under Sub- Humid Tropical Conditions - Gichimu, Bernard M.; Owuor, B. O.; Dida, M. M. (Asian Research Publishing Network (ARPN)., 2008)
Agronomic performance trial involving five cultivated watermelon accessions available in Kenya was conducted at Maseno University Research Fields for two seasons between year 2007 and 2008. The accessions included three most common commercial watermelon cultivars in Kenya namely ‘Sugarbaby’, ‘Crimson Sweet’ and ‘Charleston Gray’; one newly introduced cultivar from United States namely ‘Yellow Crimson’; and one local landrace (GBK-043014) from Kaka mega district in Western Kenya. The five were evaluated on dystric nitisols under sub-humid conditions of Maseno Division, Nyanza Province in Kenya. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Data was collected on agronomic characters including days to emergence, days to flowering, maturity period, and main vine length, number of branches on the main vine and fruit yield (number and weight). The data was subjected to analysis of variance (ANOVA) using SAS version 9.1 and differences declared significant at 5% level. Least Significant Difference (LSD5%) was used to separate the means. Linear correlation was done to compare the relationship between variables. Results demonstrated significant differences in agronomic performance between accessions. ‘Yellow Crimson’ was recommended to Kenyan growers as the best commercial cultivar with agronomic traits which leads to high yields. The landrace was found to contain various desirable agronomic traits which can be selected in future breeding programs. These include long main vine and extensive branching which were found to be highly correlated to yields. It is, however, highly seeded and its taste is unpleasant and should therefore be improved with regard to these traits.
Keywords: watermelon, commercial cultivars, agronomic performance, landrace, kenya.